Ecological Balance and Human Impact on the Natural and Environment - Nsaif Jassim, Omer (Journal of Science in Medicine and Life, 2025)
Biodiversity the variety of life at genetic, species, and ecosystem levels serves as the foundational pillar of ecosystem stability and resilience. It underpins critical ecosystem services that are indispensable for human survival, including air and water purification, nutrient cycling, soil formation, and climate regulation (Díaz et al., 2019). Despite its immense value, global biodiversity is undergoing a precipitous decline, largely driven by anthropogenic pressures. This paper examines the primary drivers of this crisis, including rampant habitat destruction due to agricultural expansion (IPBES, 2019, p. 12), pollution from industrial and urban sources, overexploitation of species, and the accelerating impacts of climate change (Urban, 2015). Through an analysis of contemporary scientific literature and global environmental assessments, this research synthesizes evidence of the profound consequences of biodiversity loss, which range from the collapse of fisheries and reduced agricultural productivity to increased vulnerability to natural disasters. Furthermore, the paper argues that the erosion of biodiversity directly threatens the achievement of the United Nations Sustainable Development Goals (SDGs), particularly those related to life on land, life below water, and climate action (Secretariat of the Convention on Biological Diversity, 2020, p. 4). In conclusion, the paper evaluates a suite of proposed sustainable solutions, emphasizing that effective conservation strategies—ranging from the expansion of protected areas and adoption of ecosystem-based management to policy reforms and international cooperation—are not merely an environmental imperative but a critical investment in long-term human well-being and economic security.